Correlation between gene polymorphisms and perioperative analgesia in patients undergoing gynecological surgery - Cai, Meng; Lei, Xiaofeng; Gan, Lin; Li, Jing; Yu, Jin (Frontiers in Genetics, 2025)
ObjectivesThis study aims to identify specific single nucleotide polymorphism (SNP) correlated to perioperative analgesia in patients undergoing laparoscopic gynecological surgery.MethodsA total of 200 females meeting specific criteria underwent gynecological laparoscopic procedures under general anesthesia. Preoperative pain sensitivity was evaluated using Pain Sensitivity Questionnaire and Pain Catastrophizing Scale (PCS). Venous blood samples were collected for SNP analysis of nine genes. The study analyzed the correlation between SNPs and pre-operative pain assessment, analgesics usage, and the occurrence of related adverse effects.ResultsSix out of nine identified loci showed polymorphisms. The PCS scores were higher in the mutation group (GG + GC) for ADRA2A rs1800544 compared to the CC group (P < 0.05). No differences were observed in visual analog scale or Ramsay sedation scores between the mutation and wild-type groups for any of the SNPs (P < 0.05). Patients in the mutant group (AG + GG) for OPRM1 rs1799971 had higher analgesic usage within 24 h compared to the wild-type group (P < 0.05). The consumption of intraoperative remifentanil was higher in the mutation group (GG + GC) of ADRA2A rs1800544 than in the CC group. The Multifactorial Dimensionality Reduction analysis suggests that the optimal interaction model includes OPRM1 rs179971 and CYP450 3A4 * 1G rs2242480 together.ConclusionPatients with GG and AG genotypes of OPRM1 rs1799971 gene required more 24-h postoperative analgesics after gynecological surgery compared to those with AA genotype. A SNP-SNP interaction was observed between OPRM1 rs179971 and CYP450 3A4 * 1G rs2242480.Clinical Trial Registration: (www.chictr.org.cn, registration number: ChiCTR2200062425)